Efficacy of Bacillus coagulans BC01 on loperamide hydrochloride-induced constipation model in Kunming mice - Zhou, Xu; Chen, Yafang; Ma, Xin; Yu, Yang; Yu, Xueping; Chen, Xiaoyong; Suo, Huayi (Frontiers in Nutrition, 2022)
In this study, the laxative effect of Bacillus coagulans BC01 (BC01) in mice was investigated using a functional constipation mouse model. 6-week-old male SPF Kunming mice were randomly divided five groups: normal group, model group, BC01 groups (high and low dose), and bisacodyl group. Except for the normal group, the functional constipation model was established by administering 0.25 mL of a loperamide hydrochloride suspension (1 mg/mL) twice daily for four consecutive days by oral gavage. After modeling, the BC01 groups were administered 0.25 mL of BC01. The bisacodyl served as a control and was administered orally at a dose of 100 mg/kg, while the other groups were administered 0.25 mL of sterile saline. After 7 days of continuous administration, the experimental mice were again induced by loperamide hydrochloride. During this period, the ability of BC01 to improve constipation symptoms in the mice was analyzed by measuring the changes in the body weight, fecal water content, small intestine propulsion rate, pathology of small intestinal tissue sections, and fecal colony diversity of the mice. The BC01 effects on preventing constipation were further evaluated by analyzing serum indices as well as mRNA and protein expression levels in the small intestinal tissue. BC01 was found to significantly promote the intestinal propulsion rate and increase the fecal water loss rate in the mice. BC01 could also alleviates constipation by regulating gastrointestinal motility (substance P, motilin, endothelin-1, somatostatin, and vasoactive intestinal peptide), gene expression (c-Kit, SCF, COX-2, NF-κB, iNOS, and eNOS), intestinal inflammation (eNOS, iNOS, NF-κB), and the intestinal flora composition in the constipated mice. In addition, the high-dose BC01 treatment had the best preventive effect on constipation. BC01 might be a potential probiotic strain to effectively relieve the adverse effects of constipation.